1996
DOI: 10.1111/j.1600-0781.1996.tb00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of cutaneous tolerance to ultraviolet B during ultraviolet B phototherapy for psoriasis

Abstract: During a schedule of multiple exposures to ultraviolet B radiation (UVB, 280-320 nm), skin develops a reduced sensitivity, variously called tolerance, photoadaptation, accommodation or acclimatization. In this study we have investigated the development of tolerance in the normal skin of a group of psoriatic patients during the course of UVB therapy. Tolerance was assessed by phototests carried out on non-lesional skin as frequently as possible throughout the treatment. Maximum tolerance was developed by the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
2
12
1
Order By: Relevance
“…Darker skin type, as expected, was protective in this study, but tanning, a significant photoprotective mechanism of human skin, has been shown in another study to be responsible for only 10% of the photoprotection in human volunteers after 4 weeks of cumulative doses of UVB 26 . Photoadaptive responses of human skin have also been measured using the minimal perceptible dose 27 …”
Section: Discussionsupporting
confidence: 68%
“…Darker skin type, as expected, was protective in this study, but tanning, a significant photoprotective mechanism of human skin, has been shown in another study to be responsible for only 10% of the photoprotection in human volunteers after 4 weeks of cumulative doses of UVB 26 . Photoadaptive responses of human skin have also been measured using the minimal perceptible dose 27 …”
Section: Discussionsupporting
confidence: 68%
“…26 Photoadaptive responses of human skin have also been measured using the minimal perceptible dose. 27 The lack of association between challenge doses of UVB and levels of adducts in this study could be explained by narrow ranges of UVB doses, variable tanning and epidermal thickening responses among individuals as well as potential experimental errors in the measurement of DNA photoproducts. However, the fact that TTT and TTC dimers moved in the same direction within individuals suggests that experimental errors are unlikely.…”
Section: Discussionmentioning
confidence: 71%
“…While dermal elastosis is described as a distinct consequence of UVR exposure (10) and hence an accurate measure of photoaging, it does not necessarily follow that it is the most appropriate standard against which to validate skin surface topography grades. Other histological changes associated with skin photoaging include thickening of the stratum corneum (11, 12), stratum granulosum (13) and epidermis (10, 14), oedematous changes to the epidermis (15), and a line of collagen fibril bundles running parallel to the skin surface in the upper papillary dermis, termed the Grenz zone (15). The present study was carried out in a community setting in Queensland, Australia, in order to assess the validity of skin surface topography grading as a measure of photoaging.…”
mentioning
confidence: 99%